MENGAMBIL HASIL DARI BARANG GADAIAN MENURUT PERSPEKTIF KH.MA.SAHAL MAHFUDZ - Muhammad Imam Haudli (Jurnal Istiqro, 2023)
The discussion of Fiqh books is usually divided into 4 major chapters which cover worship, muamalah, munakahat and jinayah. The purpose of this study seeks to examine Taking Results From Pawn Goods According to the Perspective of KH. MA. Sahal Mahfudz. This research is a qualitative descriptive study of the literature. Based on the study above, it can be concluded that the law takes advantage of goods pawned according to KH.MA.Sahal Mahfudz is unlawful because it is included in the hadith of every debt that benefits, it includes usury.